Lipoproteínas aterogénicas, factores proinflamatorios y vasculares en la enfermedad renal crónica : situaciones paradójicas - Cacciagiú, Leonardo Damián (2016)
Patients with chronic kidney disease (CKD) on hemodialysis have a markedly elevated rate of cardiovascular mortality, among 10 and 20 fold higher related to the general population. Their cardiometabolic feature usually presents paradoxical situations that do not explain the increased incidence of cardiovascular events.\nWe evaluated parameters related to lipid-lipoprotein profile, pro-inflammatory status and constituents of arterial wall by an observational, descriptive and cross-sectional design. We also carried out three in vitro experimental tests to evaluate lipoproteins functionality of and explain cytokines alterations. We included CKD patients on hemodialysis (n = 120) and healthy controls (n = 56).\nWe observed a moderate hypertriglyceridemia reflected in a accumulation of remnants lipoprotein, which was scarcely studied in this condition. VLDL were small with higher cholesterol, and had lower affinity for the enzyme that degrades it. The accumulation of triglyceride-rich lipoproteins is attributed to catabolism deficit. The decrease in LDL is paradoxical and is associated with risk of cardiovascular events, responding to curves U-shape. LDL presented qualitative alterations that increase their atherogenicity. HDL were dysfunctional and presented lower antioxidant capacity associated with lower paraoxonase activity, in addition to changes in its composition.\nAn increase in interleukin-6 and hs-CRP evidenced a subclinical inflammation, which was promoted, in part, by atherogenic lipoproteins. Adiponectin presented, paradoxically, higher values that would not exhert its anti-inflammatory role. This increase is due to decreased renal elimination, since we did not observe adiponectina expression increased in adipose tissue of rats with renal failure.\nThe factors related to the arterial wall, demonstrated, in CKD, impaired arterial function evidenced by endothelin-1 increase, phospholipase A2 activity with pro-oxidant action increase and elevated metalloproteinase-2 and -9, whole related to an active process remodeling and vulnerability of atheromatous plaques.\nThe interrelationship of these cardiometabolic parameters, several of them studied for the first time, allows us to deduce a sequence of steps that explain the accelerated atherosclerosis in CKD on hemodialysis.